A comprehensive view of existing policy directives and future interventions for water reuse in India. Issue 7 (5th July 2022) - Goyal, Kirti; Kumar, Arun
Abstract: Water reuse is one of the most sustainable water augmentation option to cope up with the high water demands of the developing communities globally. It has several additional benefits such as nutrient recovery, economic gains and environmental benefits. Even though, water reuse is economical and sustainable, its practical implementation at a wide scale has many technical, social, institutional and regulatory challenges, especially in developing countries like India. In India, there is a scarcity of stringent national regulations and guidelines for the safe implementation of wastewater reuse systems. In this study, the assessment of the existing regulatory framework for treated wastewater reuse is done to understand the need of current and future policy interventions and recommendations are made based on expert consultation. The legal assessment highlights the importance of consultation, communication and education in the development of an effective regulatory structure. The analysis of the expert reviews suggests inclusion of policy directives based on funding sources and technical infrastructure to support the growth of water reuse in India. HIGHLIGHTS: The analysis of the existing regulatory framework related to water reuse in India is done. The drawbacks of the existing policy directives have been outlined. Policy recommendations are suggested based on an extensive review and stakeholder consultation. Graphical Abstract